Mindfulness-Based Programs Improve Psychological Flexibility, Mental Health, Well-Being, and Time Management in Academics - Gabriel A. B. Marais; Sophie Lantheaume; Robin Fiault; Rebecca Shankland (MDPI AG, 2020)
(1) Background: Occupational stress is high in academia, and is partly related to time pressure. Mindfulness-based programs are known to be effective in reducing stress and increasing well-being. Recent work suggested that these programs may also improve time management. This study tested the effects of a mindfulness-based program on academics' psychological flexibility, mental health, well-being, and time management. (2) Methods: The study was conducted in a French research department. Participants were offered to join a mindfulness-based program (n = 21) or to be on a wait-list control group (n = 22). Self-reported measures of psychological flexibility, mental health (stress, anxiety, and depression symptoms), well-being, and time use were collected before and after the eight week program. (3) Results: Results showed that psychological flexibility, mental health, well-being, and efficient time use significantly increased in the intervention group compared to the control condition. (4) Conclusions: The results suggested that the mindfulness-based programs were effective in improving adaptive functioning, well-being, and optimal time use in academia, thus underlining potential useful perspectives to help academics improve mental health and time management.